Implementasi Program Pengembangan Anak Usia Dini Holistik Integratif di Satuan PAUD - Iin, Indrati; Hendrowati, Tri Yuni; Aswat, Fatqul Hajar (Universitas Muhammadiyah Surakarta, 2024)
This research is motivated by the fact that many institutions have not yet implemented the holistic integrative early childhood education (PAUD) program. The aim of this research is to understand the implementation of essential services, parental involvement, challenges and obstacles, evaluation, and the impact of the holistic integrative PAUD program in PAUD units. The method used in this research is a qualitative approach with case studies in several PAUD institutions that implement the program. Data collection was done through observation, interviews, and documentation. The results show that the implementation of the holistic integrative early childhood development program conducted at TK ABA Wates, TK ABA Wonokriyo, and TK Muslimat can meet the essential needs of children, enhance cooperation with parents in carrying out the school program, and the implementation of holistic integrative PAUD also impacts child development, the quality of institutions, and the role of parents. However, there are still challenges and obstacles, such as limitations in facilities and the competency of educators, and schools still need to conduct evaluations and monitoring to ensure the effectiveness of the holistic integrative PAUD program. The conclusion of this research emphasizes the importance of understanding, integrity, and good management, as well as ongoing support from the government and relevant stakeholders to ensure the success of early childhood development programs.